The Returns to Education over Time and the Effect of COVID-19 - Harry Anthony Patrinos; Angelica Rivera-Olvera (Institute of Labor Economics (IZA), 2024)
This paper examines the effects of the COVID-19 pandemic on the returns to education in the United States. Using data from the Current Population Survey 2011-2022, the analysis reveals that, after a period of decline, returns to education increased significantly because of COVID, particularly for men and those with university education. The returns to university for men increased by 1 percentage points. The results underscore the importance of continued investment in education to mitigate the adverse effects of future crises.
Keywords: E24; J11; J17; J31; 330; pandemics; human capital; returns to education; labor markets; COVID-19